2018
DOI: 10.1073/pnas.1717730115
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin organization by an interplay of loop extrusion and compartmental segregation

Abstract: SignificanceHuman DNA is 2 m long and is folded into a 10-μm-sized cellular nucleus. Experiments have revealed two major features of genome organization: Segregation of alternating active and inactive regions into compartments, and formation of compacted local domains. These were hypothesized to be formed by different mechanisms: Compartments can be formed by microphase separation and domains by active, motor-driven, loop extrusion. Here, we integrate these mechanisms into a polymer model and show that their i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
347
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 572 publications
(375 citation statements)
references
References 74 publications
26
347
2
Order By: Relevance
“…Furthermore, the difference is more apparent on loops of long-range (500 kb to 2 Mb) than those of short-range (300-500 kb) ( Figure 3F). [21][22][23] This phenomenon agrees with the strongest insulation across TAD boundaries during this phase as above.…”
Section: The Reconstructed Trajectory Helps To Discover the Dynamic Csupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the difference is more apparent on loops of long-range (500 kb to 2 Mb) than those of short-range (300-500 kb) ( Figure 3F). [21][22][23] This phenomenon agrees with the strongest insulation across TAD boundaries during this phase as above.…”
Section: The Reconstructed Trajectory Helps To Discover the Dynamic Csupporting
confidence: 82%
“…Obviously, the contact fraction between the same compartments increases, and the fraction between different compartments is opposite, until MS-LS phase. [21] We further merge similar stages above to obtain five larger ones with higher resolution Hi-C maps for chromatin loop detection (see the Experimental Section). These results are consistent with previous studies, but more accurately specify substages of functional or structural transitions, and more specifically characterize the dynamics of cell cycle.…”
Section: The Reconstructed Trajectory Helps To Discover the Dynamic Cmentioning
confidence: 99%
“…This model is a potential solution to the problem of enhancer–promoter search providing a mechanism through which two distally located regions of DNA can be brought into association. Computational modeling has shown that the dynamic interaction of loop‐extruding and boundary factors can recapitulate TAD patterns consistent with those observed from Hi‐C data …”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 99%
“…Computational modeling has shown that the dynamic interaction of loop-extruding and boundary factors can recapitulate TAD patterns consistent with those observed from Hi-C data. [9][10][11] The evidence for the cooperative roles of cohesin and CTCF in mediating mammalian loop extrusion is provided by a growing number of depletion and CRISPR-editing experiments. Depletion of cohesin has been shown to reduce or remove DNA looping; [6,12,13] meanwhile, CTCF depletion as well a deletion or an inversion of CTCF-binding sites more specifically disrupts domain structure.…”
Section: How Is Domain Architecture Established Across Different Orgamentioning
confidence: 99%
“…Recent studies have established the Hsp70 family of chaperone proteins as an all-purpose adenosine triphosphate (ATP) powered disassemblase, responsible for the rapid disassembly of disordered aggregates as well as of the protein coats that regulate vesicle formation in eukaryotic cells [2][3][4]. Phaseseparated intracellular droplets and granules appear to be fluidized by similar mechanisms [5,6], and even the structure of interphase chromatin seems to be set by the competition between equilibrium phase separation and active disassembly [7].…”
Section: Introductionmentioning
confidence: 99%